Hypomagnesemia, insulin secretion and action in patients without diabetes, 1 year after kidney transplantation - Carlsen, Rasmus K.; Åsberg, Anders; Svensson, My; Birkeland, Kåre I.; Jørgensen, Hanne S.; Bressendorff, Iain; Gulseth, Hanne L.; Midtvedt, Karsten; Nordheim, Espen; Jenssen, Trond G. (Frontiers in Medicine, 2025)
IntroductionHypomagnesemia after kidney transplantation has been reported as a potential risk factor for development of post-transplant diabetes mellitus.MethodsIn kidney transplant recipients undergoing an oral glucose tolerance test during one-year surveillance follow-up we estimated insulin sensitivity with the Matsuda index, a modified Stumvoll index, and HOMA-2IR. First and second phase insulin secretion was assessed using the Stumvoll equation. Participants were categorized into tertiles by plasma magnesium levels, (<0.7, 07–0.78,>0.78 mmol/L).ResultsWe included 208 patients (62% men, median age 51 years). Patients in the lowest compared to the highest magnesium tertile had higher measured GFR (mean 59 vs. 49 mL/min, p = 0.002), tacrolimus trough concentration (mean 6.7 vs. 5.5 μg/L, p < 0.001), and fasting plasma glucose (mean 5.5 vs. 5.3 mmol/L, p = 0.03). There was no significant difference in the Matsuda index between magnesium tertiles, nor in insulin sensitivity assessed by modified Stumvoll index, HOMA-2IR, first or second phase insulin. Results indicate a non-significant trend toward lower disposition index in the lowest vs. highest tertile (p = 0.052).ConclusionIn kidney transplant recipients with lower compared to normal plasma magnesium levels we found a higher fasting plasma glucose but no differences in insulin sensitivity indexes nor dynamic insulin measurements.